The U.S. Media Coverage of Islam and Muslims in the Wake of the ISIS Emergence - Alzyoud, Shlash (Eximia, 2022)
This paper seeks to describe the history of The New York Times’ coverage of Islam and Muslims in a specific period. The paper aims to look at how the newspaper represented Muslims in a time when the image of Muslims in the world was being distorted through the massacres committed by the group, ISIS, in Syria and Iraq in the name of Islam. Historical exploration focused on the coverage published in six months of 2014. The examination revealed a consistent approach with a high focus on the topics of terrorism and extremism. By far, in this period, the most prominent and widespread coverage of Muslims in the newspaper was Terrorism, ISIS, and Al Qaeda.